Нововиявлені надгробки XVIII – початку ХХ ст. з території Вознесенського кладовища міста Глухова - Мірошниченко, О.М. (Сіверщина в історії України, 2020)
Вознесенський цвинтар – один з найстаріших цвинтарів в місті Глухові. На його території збереглися надгробки кінця ХVІІІ
– початку ХХ ст. Стаття є результатом копіткої роботи по
виявленню, розчистці, проведенню обмірів, фотофіксації та ідентифікації меморіальних пам’яток ХІХ – початку ХХ ст. Автором
вводиться до наукового обігу група кам’яних плит, надгробків і їх
фрагментів, що збереглися на Вознесенському кладовищі.
У статті подано опис 55-ти надгробків кінця ХVII – початку
ХХ ст. Пам’ятки виготовлені із місцевого пісковику, різних порід
граніту та мармуру. Voznesenske Cemetery is one of the oldest in the city of Hlukhiv. On
its territory, tombstones of the late XVIII - early. XX century in the form
of chapels, plates, crosses, sculptures. The first attempts to systematize
the memorial monuments of the cemetery had a number of shortcomings.
A complete decoding of the epitaphs and a description of the tombstones
were not carried out. Also, the issue of topographic reference of objects of
study was not considered. The author took into account all the gaps and
created his own tombstone accounting system.
Our article is the result of painstaking work to identify, clear, measure,
photograph and identify memorials from the 19th - early 20th century
The author introduces into scientific circulation a group of stone slabs,
tombstones and their fragments, preserved at the Ascension Cemetery
of the town of Hlukhiv. The article describes fifty-five tombstones of the
late XVIII begining XX century, made of local sandstone, various rocks
of granite and marble.
The extreme chronological framework of the graves of 1788-1964.
Ancient tombstones of the Voznesenske Cemetery are threatened by natural
and anthropogenic factors. Ancient monuments that interfere with the
townspeople are dismantled, smashed, and taken out of the cemetery.
The results of the study will be interesting to local historians, historians,
ethnographers, monuments and geneologists. The surviving stone gravestones
from local sandstone is a sample of the production of Hlukhiv masons. This
craft is dead in our region, therefore, every discovered monument needs to
be preserved and maintained.